Advanced maternal age causes premature placental senescence and malformation via dysregulated α‐Klotho expression in trophoblasts. Issue 7 (9th June 2021) - Chen, Zhi; Xiong, Liling; Jin, Huili; Yu, Jiaxiao; Li, Xin; Fu, Huijia; Wen, Li; Qi, Hongbo; Tong, Chao; Saffery, Richard; Kilby, Mark D.; Baker, Philip N.
Abstract: Advanced maternal age (AMA) pregnancy is associated with higher risks of adverse perinatal outcomes, which may result from premature senescence of the placenta. α‐Klotho is a well‐known antiaging protein; however, its expression and effect on the placenta in AMA pregnancies have not yet been fully elucidated. The expression patterns of α‐Klotho in mouse and human placentas from AMA pregnancies were determined by Western blotting and immunohistochemistry (IHC) staining. α‐Klotho expression in JAR cells was manipulated to investigate its role in trophoblastic senescence, and transwell assays were performed to assess trophoblast invasion. The downstream genes regulated by α‐Klotho in JAR cells were first screened by mRNA sequencing in α‐Klotho‐knockdown and control JAR cells and then validated. α‐Klotho‐deficient mice were generated by injecting klotho ‐interfering adenovirus (Ad‐Klotho) via the tail vein on GD8.5. Ablation of α‐Klotho resulted in not only a senescent phenotype and loss of invasiveness in JAR cells but also a reduction in the transcription of cell adhesion molecule (CAM) genes. Overexpression of α‐Klotho significantly improved invasion but did not alter the expression of senescence biomarkers. α‐Klotho‐deficient mice exhibited placental malformation and, consequently, lower placental and fetal weights. In conclusion, AMA results in reduced α‐Klotho expression in placental trophoblasts, therefore leading to premature senescence and loss of invasion (possibly through the downregulation of CAMs), both of which ultimately result in placental malformation and adverse perinatal outcomes. Abstract : Advanced maternal age is an independent risk factor for the loss of placental α‐Klotho expression beginning in the early phase of pregnancy. α‐Klotho deficiency in trophoblast not only induces senescence but also suppresses trophoblast invasion by downregulating the expression of cell adhesion molecules, both of which lead to maldevelopment of placenta, and ultimately result in higher risk of adverse perinatal outcomes